Knockdown of FBI-1 Inhibits the Warburg Effect and Enhances the Sensitivity of Hepatocellular Carcinoma Cells to Molecular Targeted Agents via miR-3692/HIF-1α - Liu, Juan; Yang, Chao; Huang, Xiao-Mei; Lv, Pan-Pan; Yang, Ya-Kun; Zhao, Jin-Na; Zhao, Si-Yuan; Sun, Wan-Jun (Frontiers in Oncology, 2021)
Knockdown of FBI-1 inhibits the Warburg effect and enhances the sensitivity of hepatocellular carcinoma cells to molecular targeted agents via miR-3692/HIF-1α